The Collaborative Pulse Of Healthcare: A Critical Analysis Of Nursing’s Role In A Holistic Approach To Patient Care Across Medical Specialties (The Review of Diabetic Studies, 2024)
This critical analysis explores nursing's pivotal role in fostering a holistic approach to patient care within multidisciplinary healthcare teams. As healthcare becomes increasingly complex, the integration of collaborative practices across specialties is essential for delivering comprehensive and patient-centered care. Nurses, often serving as the main touchpoint for patients, play a crucial role in coordinating care, advocating for patient needs, and bridging communication among healthcare professionals. This study examines the specific contributions of nurses, identifies challenges in inter-professional collaboration, and highlights enablers that support effective teamwork. Findings suggest that nursing collaboration positively impacts patient outcomes, satisfaction, and care continuity, though challenges such as communication barriers and hierarchical structures remain. By enhancing support for collaborative nursing roles, healthcare institutions can achieve improved quality of care and greater efficiency. Recommendations include promoting interdisciplinary training, clarifying team roles, and implementing policy reforms to empower the nursing workforce in holistic patient care.